Pre-Clinical Studies with D-Penicillamine as a Novel Pharmacological Strategy to Treat Alcoholism: Updated Evidences - Orrico, Alejandro; Martí-Prats, Lucía; Cano-Cebrián, María J.; Granero, Luis; Polache, Ana; Zornoza, Teodoro (Frontiers in Behavioral Neuroscience, 2017)
Ethanol, as other drugs of abuse, is able to activate the ventral tegmental area dopamine (VTA-DA) neurons leading to positively motivational alcohol-seeking behavior and use, and, ultimately to ethanol addiction. In the last decades, the involvement of brain-derived acetaldehyde (ACD) in the ethanol actions in the mesolimbic pathway has been widely demonstrated. Consistent published results have provided a mechanistic support to the use of ACD inactivating agents to block the motivational and reinforcing properties of ethanol. Hence, in the last years, several pre-clinical studies have been performed in order to analyze the effects of the sequestering ACD agents in the prevention of ethanol relapse-like drinking behavior as well as in chronic alcohol consumption. In this sense, one of the most explored interventions has been the administration of D-Penicillamine. These pre-clinical studies, that we critically summarize in this article, are considered a critical step for the potential development of a novel pharmacotherapeutic strategy for alcohol addiction treatment that could improve the outcomes of current ones. Thus, on one hand, several experimental findings provide the rationale for using DP as a novel therapeutic intervention alone and/or in combination to prevent relapse into alcohol seeking and consumption. On the other hand, its effectiveness in reducing voluntary ethanol consumption in long-term experienced animals still remains unclear. Finally, this drug offers the additional advantage that has already been approved for use in humans, hence it could be easily implemented as a new therapeutic intervention for relapse prevention in alcoholism.